THE POTENTIAL OF INTERACTIVE GAMES IN TEACHING ENGLISH IN PRESCHOOL INSTITUTIONS - Bayjanov Saparniyaz (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: The use of interactive games in teaching English to preschool children has gained increasing relevance, particularly within Uzbekistan’s evolving educational landscape. This article examines the pedagogical and developmental benefits of integrating interactive games into early childhood English education. Drawing upon established learning theories, such as those of Piaget, Vygotsky, and Krashen, it highlights the ways in which games align with cognitive, emotional, and linguistic needs of young learners. The article discusses various types of games—physical, digital, role-play, and musical—and how they contribute to vocabulary development, communication skills, and motivation. Through an analysis of current practices in Uzbekistan, both urban and rural settings are explored, identifying achievements and limitations. The study also proposes solutions for challenges such as teacher preparedness, resource scarcity, and culturally relevant content. Ultimately, this article argues that interactive games are not only effective tools for English language acquisition but also support holistic child development. Practical recommendations are provided to enhance the implementation of such strategies within Uzbekistan’s preschool institutions. This research is particularly valuable for educators, policymakers, and curriculum developers seeking to create engaging, child-centered language environments. The approach bridges global pedagogical frameworks with local educational needs.